Pacific literatures as world literature - Lin, Chia-hua (Chia-hua Yvonne); Huang, Hsinya (New York Bloomsbury Academic, 2023)
Pacific Literatures as World Literature is a conjuration of trans-Pacific poets and writers whose work enacts forces of “becoming oceanic” and suggests a different mode of understanding, viewing, and belonging to the world. The Pacific, past and present, remains uneasily amenable to territorial demarcations of national or marine sovereignty. At the same time, as a planetary element necessary to sustaining life and well-being, the Pacific could become the means to envisioning ecological solidarity, if compellingly framed in terms that elicit consent and inspire an imagination of co-belonging and care. The Pacific can signify a bioregional site of coalitional promise as much as a danger zone of antagonistic peril.

With ground-breaking writings from authors based in North America, Japan, Taiwan, Korea, Hawaii, and Guam and new modes of research – including multispecies ethnography and practice, ecopoetics, and indigenous cosmopolitics – authors explore the socio-political significance of the Pacific and contribute to the development of a collective effort of comparative Pacific studies covering a refreshingly broad, ethnographically grounded range of research themes. This volume aims to decenter continental/land poetics as such via long-standing transnational Pacific ties, re-worlding Pacific literature as world literature.
Foreword : A writer's ocean / Syaman Ranpongan -- Introduction / Xinya Huang and Chia-hua Lin -- Colonialism : the Pacific Ocean. The Wilkes expedition (1838-1842) and the formation of a U.S. empire of bases in the Pacific / John R. Eperjesi -- Epeli Hau'ofa's pronouns / Paul Lyons -- Mountains of Taiwan, Japanese colonization, and Western science / Chia-Li Kao -- Demilitarization and decolonization in Chamoru literature from Guåhan (Guam) / Craig Santos Perez -- Indigenous resistance to colonialism. Decolonizing Guam with poetry : "everyday objects with mission" in Craig Santos Perez's poetry / Anna Erzebet Szucs -- Remapping Mānoa Valley in Hawaiian literature / Chia-hua Lin -- Planetary boundaries, planetary imaginaries : homing Pacific eco-poetry / Xinya Huang -- The ecological vision of the Ainu reflected in their oral tradition / Hitoshi Oshima -- Ocean and ecology. Becoming Oceania: towards a planetary ecopoetics, or Reframing the Pacific Rim / Rob Wilson -- Island imaginations, bioregionalism, and the environmental humanities / Kathryn Yalan Chang -- Decolonizing Oceanic realms : voices from Australia Pacific / Iris Ralph -- Whale as cosmos : multi-species ethnography and contemporary indigenous cosmopolitics / Joni Adamson.
Includes bibliographical references and index.
Keywords: Pacific Island literature -- History and criticism; Pacific Island poetry -- History and criticism